Dynamic Modeling and Analysis of Earth Fault Detection Systems in Power Transmission - Danladi, Muhammad Nazif; Bal, Yakubu Barau; Muhammad, Fatima (Darul Yasin Al Sys, 2025)
This study presents a comprehensive approach to the modeling, simulation, and analysis of single line-to-ground (SLG) fault detection in high-voltage power transmission systems. A dual-unit detection system was developed, integrating a MATLAB/Simulink-based simulation model with a microcontroller-based hardware unit for real-time fault identification and communication. The simulation model replicates the behavior of a 132 kV transmission line under various SLG fault conditions, while the hardware unit employs voltage and current sensors connected to an Arduino Uno and GSM module to detect faults and transmit location alerts. Experimental procedures included controlled fault injection, waveform analysis, and algorithmic fault distance estimation using zero-sequence currents and voltage dips. Simulation outcomes demonstrated high location accuracy, with error rates consistently below 0.75% across a fault distance range of 30–300 km. The system exhibited fast response times, high precision, and cost-effectiveness, indicating strong potential for deployment in power grids of developing regions. The integrated software-hardware architecture offers a scalable and efficient solution for minimizing downtime and enhancing fault response coordination in transmission networks.